Strategi Kesopanan Berbahasa terhadap Kemampuan Tindak Tutur Mahasiswa Program Studi Pendidikan Bahasa Inggris Universitas Muhammadiyah Metro - Dedy Subandowo; Fenny Theresia (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2014)
This research is entitled The Strategy of Language Politness toward Students Speech Act Ability in English Education Study Program of Muhammadiyah University of Metro. It aims to find out the politness strategy toward students speech act ability and the usage of language politeness toward students speech act ability in speaking interaction in Muhammadiyah University of Metro. This is a descriptive qualitative research. The population of data is taken from the students of the fifth semester in Muhammadiyah University of Metro. The data collecting technique of this reasearch is noting and Participative observation technique. Data analysis technique uses pragmatic identity method. The result of data analysis is come out with informal forms. The result shows that there are three kinds of speech act strategy in language communication; namely 1) locutionary, 2) ilocutionary, and 3) perlucutionary act. The language usage of politness can be devided into direct and indirect spech and it covers reason, apology,gratitude, and request. Keywords: language politness strategy, speech act, sociopragmatics